Interactions between Zoopthora radicans and Pandora blunckii isolates in Plutella xylostella populations - Guzmán-Franco, A.W. (2005)
The interactions between isolates of the entomopathogenic fuingi Zooplithora radicans and Pandora blunckii in Plutella xylostella populations NNerc investigated. A series of experiments were carried out to detect major differences amongst isolates from each species, these included in vitro growth at different temperatures, in vitro intra and inter -specific interactions and genetic variability based on the internal transcribed spacer regions of the ribosomal DNA (rDNA-ITS). All the isolates showed different in vitro growth profiles at different temperatures (Chapter 2). Isolates with greater and smaller growth rates were selected for further experiments. The intra and inter-specific interactions in vitro were investigated using these selected isolates (Chapter 31). Overall, P. blunckii was more competitive than Z. radicans. The negative effect of some P. blunckii isolates on the in vitro growth of Z. radicans isolates was consistent over the two temperatures evaluated. This suggested that temperature did not have a significant effect on the outcomes. Particular isolates were selected based on their differential competitive abilities for further experiments. The genetic variability amongst isolates of Z. radicans (39 isolates) and P. blunckii (22 isolates) was examined (Chapter 4). ITS-RFLP analysis using the ITS rDNA region did not show differences amongst P. blunckii isolates, but large differences were found amongst the Z. radicans isolates. Sequence information of the ITS rDNA regions of Z. radicans isolates from different RFLP groups confirmed intra-specific genetic variability. The sequence information obtained allowed to develop species-specific primers for the detection of both pathogens using conventional PCR. The species-specific primers developed for Z. radicans could be optimized for use in quantitative real-time PCR, but not the P. blunckii species-specific primers (Chapter 6). The interactions between four selected isolates infecting P. xylostella larvae were investigated under different conditions (Petri dishes and on Chinese cabbage plants) and dose proportions (Chapter 5). The species with a numerical disadvantage in dose at inoculum was more likely to be excluded regardless of virulence, which was previously estimated for each Chapter 5. Both species were able to co-exist in individual larva via scramble competition, but a reduction in fitness was found because both species produced fewer conidia or resting spores than when they were inoculated singly. The Interactions during the infection process were also determined (Chapter 6). The outcomes were based on the quantities of fungal DNA determined using real-time PCR of Z. radicans either single or dual-inoculated with P. blunckii at different day 5 postinoculation. During the infection process, Z. radicans growth was stimulated within the host as a response to the presence of P. blunckii at day 3 and 4 of the infection (parasitic phase). However, at day 5 (saprophytic phase), P. blunckii out-competed Z. radicans. The production of resting spores by some isolates of Z. radicans seems to be an efficient strategy to survive direct competition against a more virulent species. The negative effect of the interactions between these two fungal pathogens found in this study, suggest that the use of both pathogens simultaneously in the field for the microbial control of P. 1-xysostella should be reconsidered. Although mortality of the host is obtained, the persistence and survival of both pathogens is negatively affected.